Eco Bricks: Ladrillos Ecológicos elaborados con mascarillas quirúrgicas desechables - Bonilla Coca, Michelle Caroline (2021)
Nowadays the production of medical waste has increased as the health crisis declared, however, the use of personal protective equipment in hospitals and medical centers is constant, thus generating waste that is disposed of in sanitary landfills whose decomposition can take years, likewise, this accumulation creates the need to generate large spaces with a negative impact on the environment; this study addresses important aspects related to environmental damage: the accumulation of solid waste of this type and the impact generated by the traditional production process of ceramic bricks. The present study aims to develop a process for the reuse of surgical masks through the use of mask membranes as a partial substitute for the cement implemented in the production of ecological bricks; two possible dosages to be applied are indicated in which additions of 5, 10 and 15% of mask membranes are used, as well as samples whose dosage does not present the use of membranes. During this research, the mechanical characteristics of ecological bricks with the addition of membranes from surgical masks were evaluated, which compared with the requirements of the technical standards in force in our country. The results show an optimal dosage with the use of 10% of mask membranes, obtaining compressive strengths of 20 MPa, an average absorption of 12% and a density of 1.73 g/cm3.